Influences of pulse laser parameters on properties of AISI316L stainless steel thin-walled part by laser material deposition. (1st July 2017) - Wang, Xinlin; Deng, Dewei; Yi, Hongli; Xu, Haiyan; Yang, Shuhua; Zhang, Hongchao
Abstract: Laser material deposition (LMD) which combines laser cladding and rapid prototyping technique has been widely used to build full density metal parts directly without using modules or tools. There are many parameters affecting the quality and properties of the LMD parts through changing the energy distribution. Pulse laser provides the user an added degree of controlling over the energy distribution which seriously affects the solidification of molten pool and eventual part formation. In the present study, a series of AISI316L stainless steel thin-walled parts are successfully produced by LMD with different pulse laser parameters to investigate the effects of energy distribution on characteristics (microstructure, hardness, residual stress and tensile properties). The results show that the characteristics of LMD parts are obviously influenced by laser mode (pulse or continuous wave laser) and pulse laser parameters (T_pulse and T_pause). The microstructure of parts presents various grain sizes with the different pulse laser parameters. The different value (D-value) between the hardness of edge and central region varies considerably with the pulse laser parameters. The maximum D-value of hardness is presented in the part deposited by continuous wave laser. The maximum hardness is presented in item 4 (T_pulse=10 ms, T_pause=10 ms) and the minimum hardness is presented in part fabricated by continuous wave laser where the residual stress on Z-component presents tensile stress at the edge region and compress stress at the central region but opposite trend happens to the residual stress on Y-component. Tensile stress on Z-component at the edge region increases even presents compress tensile with the decrease of T_pulse. The stress on Y-component presents a periodic variation between tensile stress and compress stress in the Y-direction of the part fabricated by pulse laser. The ultimate tensile strength (UTS) of the part fabricated using pulse laser is higher than the part fabricated using continuous wave laser. The specimens paralleled to scanning speed present higher UTS values but lower elongation than the specimens perpendicular to scanning speed. Highlights: The maximum D-value is presented in the part by continuous wave laser. The residual stress is obviously affected by pulse laser parameters. The UTS of the part is more superior by pulse laser.